Quality Analysis of Kiwifruit Cultivars in Mid Hill Condition of Lumle, Nepal - Poudel, Shyam Prasad; Somai, Kajol; Timilsina, Chandrakanta; Basnet, Resham Bahadur; Upadhaya, Kalika Prasad; Gautam, Janarjan (Nepalese Journal of Agricultural Sciences, 2025)
This study conducted at the Directorate of Agricultural Research (DoAR), Lumle, Kaski (1650m asl) from 2022 to 2023, evaluated the quality attributes of four kiwifruit cultivars: ‘Hayward Oblong’, ‘Hayward Oval’, ‘Allison’, and ‘Bruno 2’. Mature fruits, ripened for two weeks using local ethylene-releasing agents, were analyzed for physical characteristics (individual fruit weight, 5-fruit weight, length, diameter, diameter-to-length ratio) and chemical properties (Total Soluble Solids (TSS) and Titratable Acidity (TA)). Data were statistically analyzed using ANOVA and Duncan’s Multiple Range Test. Results revealed significant genotypic variation: ‘Bruno-2’ consistently showed superior individual fruit weight (28.00g in 2022, 46.1g in 2023) and higher TSS (10.92°Brix in 2022, 15.96°Brix in 2023), while ‘Hayward Oval’ was rounder (diameter/length ratio 1.01 in 2022, 0.89 in 2023) with higher acidity (1.97% TA in 2022, 2.19% TA in 2023). All cultivars exhibited increased fruit weights in 2023, suggesting improved conditions.